1994
DOI: 10.1002/mrm.1910310502
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro31P magnetic resonance spectroscopic studies of the hepatic response of healthy rats and rats with acute hepatic damage to fructose loading

Abstract: The hepatic response to a fructose challenge for control rats, and rats subjected to an acute sublethal dose of carbon tetrachloride (CCl4) or bromobenzene (BB), was compared using dynamic in vivo 31P MRS. Fructose loading conditions were used in which control rats showed only a modest increase in hepatic phosphomonoester (PME), and a small decrease in ATP, Pi, and intracellular pH after fructose administration. Both CCl4 and BB-treated rats showed a much greater fructose-induced accumulation of PME than did c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Mann et al (43) through relief of biliary obstruction and Leij‐Halfwerk et al (44) through infusion of intravenous ATP). Finally, some investigators have used the infusion of intravenous fructose (or d ‐tagatose, a stereoisomer of d ‐fructose (38)) to further study hepatic energy metabolism (39, 40). Since intravenous fructose uniformly depletes hepatic ATP, some research suggests that the measurement of ATP recovery can serve as a dynamic ‘hepatic energy stress test’ (Table 2, fructose studies), with impaired livers demonstrating slower recovery.…”
Section: Data Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mann et al (43) through relief of biliary obstruction and Leij‐Halfwerk et al (44) through infusion of intravenous ATP). Finally, some investigators have used the infusion of intravenous fructose (or d ‐tagatose, a stereoisomer of d ‐fructose (38)) to further study hepatic energy metabolism (39, 40). Since intravenous fructose uniformly depletes hepatic ATP, some research suggests that the measurement of ATP recovery can serve as a dynamic ‘hepatic energy stress test’ (Table 2, fructose studies), with impaired livers demonstrating slower recovery.…”
Section: Data Interpretationmentioning
confidence: 99%
“…Various studies with disparate aims also seem to yield a consistent conclusion about ATP levels: (38)) to further study hepatic energy metabolism (39,40). Since intravenous fructose uniformly depletes hepatic ATP, some research suggests that the measurement of ATP recovery can serve as a dynamic 'hepatic energy stress test' ( Table 2, fructose studies), with impaired livers demonstrating slower recovery.…”
Section: Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra acquired using a 10-s relaxation delay indicated that the phosphorous metabolites were fully relaxed using a 5-s delay, and that nuclear Overhauser enhancement of the phosphorus resonances were minimal. Chemical shifts were referenced to glycerolphosphocholine at −0.13 ppm (Merchant et al, 1999), and the tentative peak assignments were made based on previously published reports (Bell et al, 1993;Changani et al, 1999;Changani et al, 1996;Harvey et al, 1999;Lu et al, 1994;Gillham and Brindle, 1996;Williams et al, 1998). Metabolite peak areas were computed using the instrument software.…”
Section: P Spectroscopy Of Hydrophilic Metabolitesmentioning
confidence: 99%
“…The complicated monoester region of the spectrum is expanded in Figure 5. Metabolites were identified based on chemical shift values taken from previous literature reports (Bell et al, 1993;Changani et al, 1999;Changani et al, 1996;Gillham and Brindle, 1996;Harvey et al, 1999;Lu et al, 1994;Williams et al, 1998). Metabolites quantified for this investigation are 6-phosphogluconate (6PG), 4.92 ppm; glucose-6-phosphate (G6P), 4.51 ppm; glycerol-3-phosphate (G3P), 4.44 ppm; phosphoglycerate (PG), 4.10 ppm; fructose-6-phosphate ( ppm.…”
Section: Phosphoenergeticsmentioning
confidence: 99%